2017
DOI: 10.1371/journal.pone.0173688
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of bone scintigraphy for the diagnosis of Complex Regional Pain Syndrome 1: A systematic review and Bayesian meta-analysis

Abstract: BackgroundSince 2007, the Budapest criteria are recommended for the diagnosis of Complex Regional Pain Syndrome (CRPS) 1. The usefulness of bone scintigraphy (BS, index test) for the diagnosis of CRPS 1 remains controversial. Imperfect reference tests (RT) result in underestimation of the diagnostic accuracy of BS. Further, biased results can occur when a dependency between the RT and BS exists.The objective was to assess the impact of different RTs, specifically the Budapest criteria, and the assumed imperfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 47 publications
0
15
0
2
Order By: Relevance
“…Bone scintigraphic abnormalities may be seen in patients with complex regional pain syndrome (CRPS), formerly known as reflex sympathetic dystrophy [95][96][97]. Meta-analyses have found only moderate concordance between bone scintigraphy and the presence or absence of CRPS [98], and low sensitivity for detection of CRPS when compared to clinical diagnostic criteria [99][100][101]. Bone scintigraphic does have high specificity, and can be used to rule out CRPS [101].…”
Section: Discussion Of Procedures By Variant Variant 1: Atraumatic Shmentioning
confidence: 99%
“…Bone scintigraphic abnormalities may be seen in patients with complex regional pain syndrome (CRPS), formerly known as reflex sympathetic dystrophy [95][96][97]. Meta-analyses have found only moderate concordance between bone scintigraphy and the presence or absence of CRPS [98], and low sensitivity for detection of CRPS when compared to clinical diagnostic criteria [99][100][101]. Bone scintigraphic does have high specificity, and can be used to rule out CRPS [101].…”
Section: Discussion Of Procedures By Variant Variant 1: Atraumatic Shmentioning
confidence: 99%
“…When utilised for evaluating CRPS I, bone scintigraphy imparts a high specificity, but sensitivity was found to be decreased when using the Budapest criteria as a reference. 43 Another recent meta-analysis concluded that scintigraphy has no benefit in the management of CRPS, as it should not be used as a confirmatory measure. 44 Electromyography has shown some validity in specific patient populations.…”
Section: Other Diagnostic Toolsmentioning
confidence: 99%
“…19 This test, particularly phase 3, is highly specific, especially for the upper limb, [18][19] but when applied in patients with CRPS diagnosed with the Budapest criteria, the sensitivity is quite poor (0.551). 20 In conjunction with the TPBS imaging, serum osteoprotegerin, an osteoblast activity marker, could be used as a diagnostic tool with a sensitivity about 0.74 and a specificity of 0.8. 21 There was a significant positive correlation between increased radiotracer uptake in TPBS phase 3 and serum osteoprotegerin in patients with CRPS suggesting an increased osteoblast activity.…”
Section: Diagnosismentioning
confidence: 99%